Design and Implementation of Nanotechnology QCA Geometric Greedy Router - Lamjed Touil; Ismail Gassoumi; Abdellatif Mtibaa (Journal of Electrical and Computer Engineering)
This paper presents an optimized geometric greedy router (GGR) based on quantum dot cellular automata (QCA) technology. The proposed structure of GGR is based on a spanning tree of the network. This type of communication does not require an IP address. It uses only local information and can be used in many communication devices. In this paper, we first describe the principal components of the router and then we present their QCA architecture. The QCA technology is the most likely alternative to replace conventional circuits (CMOS) due to their very low power consumption and high processing speed. To consider integration with other complex circuit, we have utilized QCA clock-phase-based technique for the proposed design architecture. The results obtained using the QCA designer tool exhibit the superiority of the presented architecture over the existing designs. The proposed structure shows a reduction of 30% reduction in occupied space. The power dissipation rate of the proposed design is analyzed by QCAPro tool to approve its reliability.